2021
DOI: 10.1088/1755-1315/910/1/012077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenylalanine, Jasmonic Acid and Biofertilizer on Growth, Yield and Anthocyanin Pigments of Roselle Calyces

Abstract: Experiment was conducted during summer season of 2021 to study the effect of foliar applications of Phenylalanine (Phe), Jasmonic acid (JA), Biofertilizer (Bio) and their combinations (Phe+JA, Phe+Bio, JA+Bio, Phe+JA+Bio and control) on some growth, yield parameters and anthocyanin compounds on Roselle calyces Hibiscus sabdariffa L., The treatments were distributed on Randomized Completely Block Design in three replicates, means were compared according to the Least Significant Difference test (LSD) at probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Increasing salicylic acid concentrations sprayed on plants to 300 mg l-1 caused an increase in plant height, branches number, and volatile oil percentage, total chlorophyll content in leaves, as showed in Tables (1, 2, 3, and 5). Whereas, increasing the concentrations of SA sprayed on plants to 150 and 300 mg l-1 caused a significantly increase of production volatile oil per plant as shown in Tables (5). These results can be explained by the stimulating effect on regulating plant physiological and biochemical processes such as cell division, differentiation and elongation, as well as, it stimulates the absorption of elements and control of their transition, increase the permeability of cellular membranes of ions, accelerate the process of carbon and protein synthesis and increases the activity of enzymatic processes of photosynthesis (Raskin,1990; & El-Tayeb, 2005), the increase in plant height possibly as a result of SA ability to increase the amount of internal hormones like gibberellin, auxin, and cytokinin in plants, which in turn promotes cell division and elongation and, eventually, plant growth and development (Hayat & Ahmed, 2007).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Increasing salicylic acid concentrations sprayed on plants to 300 mg l-1 caused an increase in plant height, branches number, and volatile oil percentage, total chlorophyll content in leaves, as showed in Tables (1, 2, 3, and 5). Whereas, increasing the concentrations of SA sprayed on plants to 150 and 300 mg l-1 caused a significantly increase of production volatile oil per plant as shown in Tables (5). These results can be explained by the stimulating effect on regulating plant physiological and biochemical processes such as cell division, differentiation and elongation, as well as, it stimulates the absorption of elements and control of their transition, increase the permeability of cellular membranes of ions, accelerate the process of carbon and protein synthesis and increases the activity of enzymatic processes of photosynthesis (Raskin,1990; & El-Tayeb, 2005), the increase in plant height possibly as a result of SA ability to increase the amount of internal hormones like gibberellin, auxin, and cytokinin in plants, which in turn promotes cell division and elongation and, eventually, plant growth and development (Hayat & Ahmed, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…The outcomes in Table (5) demonstrated that spraying Rosemary plant with Gibberellic acid at 400 mg l-1 caused significantly increased in chlorophyll content in leaves reaching 20.25 mg g-1 f.w. Furthermore, increased salicylic acid concentrations sprayed on the plants increased the values of this characteristic significantly from 22.08 to 23.65 and 25.72 mg g-1 f.w for 0, 150, and 300 mg l-1 SA respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we also found a role for JA in the plant growth state at the same time. In previous studies, we found that large amounts of exogenous JA cause stunted plant growth [ 61 ], while moderate amounts promote plant growth [ 62 ]. Even in the JAZ family, there are important genes that can regulate the morphology of the plant and accelerate its flowering [ 33 ].…”
Section: Discussionmentioning
confidence: 99%